1987
DOI: 10.1007/bf01905168
|View full text |Cite
|
Sign up to set email alerts
|

DSC of sun-exposed chloroquine phosphate

Abstract: Pharmaceutical intended for use in the tropics are required to maintain their stability under the most severe storage conditions. Chloroquine phosphate, a common antimalarial formulation, was exposed to the sun of the roof topunder the extreme heat of the Saharan climate during the hot and dry season (February to June) at an average day temperature of 43 ~ The heat of melting A H determined by differential scanning calorimetry decreased from 60.1 J/g to 33.2 J/g after exposure for 73 days, corresponding to 49%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We employ the "global ethnography" methodology put forward by Burawoy et al, 42 which allows us to transcend the local focus of traditional ethnography to embrace analyses that incorporate broader geographical and historical processes that influence and elicit responses from the local. In the context of the time-space compression that defines the information and communication technologies(ICT)globalization nexus, it is important that the ethnographic scope of the study be global even as it focuses on the study of specific locales.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We employ the "global ethnography" methodology put forward by Burawoy et al, 42 which allows us to transcend the local focus of traditional ethnography to embrace analyses that incorporate broader geographical and historical processes that influence and elicit responses from the local. In the context of the time-space compression that defines the information and communication technologies(ICT)globalization nexus, it is important that the ethnographic scope of the study be global even as it focuses on the study of specific locales.…”
Section: Methodsmentioning
confidence: 99%
“…41 It is not surprising, therefore, to hear of Africa's marginalization in the prevailing discourse on globalization. 42 At the same time, as feminist scholars have long reminded us-through such terms as situated knowledge and God-trick 43 -"what we see depends on where we are looking from." 44 In what follows, it will be demonstrated that when one looks at Africa's ties with globalization from the standpoint of religion, in particular, the picture that emerges is different.…”
Section: A Chorus Of Afropessimism Under Contemporary Globalizationmentioning
confidence: 99%
See 3 more Smart Citations